2021
DOI: 10.1001/jamanetworkopen.2021.0684
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Latinx Individuals Hospitalized for COVID-19

Abstract: IMPORTANCE Latinx individuals, particularly immigrants, are at higher risk than non-Latinx White individuals of contracting and dying from coronavirus disease 2019 (COVID-19). Little is known about Latinx experiences with COVID-19 infection and treatment. OBJECTIVE To describe the experiences of Latinx individuals who were hospitalized with and survived COVID-19. DESIGN, SETTING, AND PARTICIPANTS The qualitative study used semistructured phone interviews of 60 Latinx adults who survived a COVID-19 hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
183
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(198 citation statements)
references
References 26 publications
6
183
0
Order By: Relevance
“…It is a retrospective observational study, conducted with data from a single center, in a public health system, and with a limited sample size. We do not have data on certain epidemiological factors [ 3 , 4 , 12 , 13 ] (such as the number of cohabiting persons, patients’ current jobs or education level), which may impede the interpretation of the results. Data availability was limited to the electronic medical records at our institution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a retrospective observational study, conducted with data from a single center, in a public health system, and with a limited sample size. We do not have data on certain epidemiological factors [ 3 , 4 , 12 , 13 ] (such as the number of cohabiting persons, patients’ current jobs or education level), which may impede the interpretation of the results. Data availability was limited to the electronic medical records at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that COVID-19 infections could be more frequent among people of Latin American origin than among Europeans, and that both the need for hospital admission and instances of mortality would also be more frequent among them [ 1 , 2 , 3 , 4 , 5 ]. Deaths attributed to COVID-19 among Latin/Hispanic people in the USA are estimated to be 110.005 (18.4% of the total rate) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the Latin Americans in our study experienced severe/critical disease more frequently than immigrants from other regions because they knew less about or underestimated the early signs of COVID-19 and were therefore less likely to seek medical advice promptly, or they may have been afraid of losing wages or their often precarious and unregistered jobs. These factors were found to be common in a qualitative study of Latin Americans with COVID-19 hospitalised in San Francisco [23], and may explain the excess burden of morbidity and mortality among Latin Americans in the USA, particularly in more recent immigrants [24,25].…”
Section: Discussionmentioning
confidence: 98%
“…At JAMA Network Open, we are making concerted efforts to right these wrongs and are cognizant that our efforts must evolve and expand over time. We will continue to publish studies [12][13][14] and commentaries [15][16][17] that examine the innumerable ways in which racism affects health and health care, and the potential means to mitigate these effects. Ten months ago, we issued a call for papers on the effects of systemic racism in health.…”
mentioning
confidence: 99%